Biracial in America : Forming and Performing Racial Identity. - Khanna, Nikki (Rowman & Littlefield Pub. Group, 2011)
Elected in 2008, Barack Obama made history as the first African American President of the United States. Though recognized as the son of his white Kansas-born mother and his Kenyan father, the media and public have nonetheless pigeonholed him as black, and he too self-identifies as such. Obama's experiences as a biracial American with black and white ancestry, although compelling because of his celebrity, however, is not unique and raises several questions about the growing number of black-white biracialAmericans today: How are they perceived by others with regard to race? How do they tend to.